Cities in a globalizing world : governance, performance and sustainability - Léautier, Frannie (WBI learning resources series., 2006)
Annotation 'Cities in a Globalizing World' stresses that quality of governance can determine whether the burgeoning cities of the developing world can become global centers of opportunity or urban examples of over crowding and underachievement. The book examines cases where the forces of globalization, urbanizations, and governance come together most successfully. It demonstrates that services tend to be better where citizens have access to information on the budget (a measure of transparency and accountability) or where information was available on how to start a business (a measure of transparency and responsiveness to firms). The book is intended to guide city managers on various ways of enhancing services and human resources, which will, in turn, attract trade, finance, and tourism to boost economic growth.